2008
DOI: 10.1189/jlb.1107778
|View full text |Cite
|
Sign up to set email alerts
|

The influence of IL-2 family cytokines on activation and function of naturally occurring regulatory T cells

Abstract: IL-2 is essential for CD4+CD25+forkhead box P3+ (FoxP3+) naturally occurring regulatory T cell (Treg) homeostasis and activation. Binding of IL-2 to its receptor leads to phosphorylation of STAT5, and binding of phosphorylated STAT5 to the foxp3 promoter increases foxp3 transcription, resulting in elevated levels of FoxP3 protein in Tregs. Transcriptional regulation by the elevated levels of FoxP3 is thought to be essential for the strong suppressor function seen in activated Tregs. IL-2 belongs to a family cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
65
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(71 citation statements)
references
References 52 publications
5
65
0
1
Order By: Relevance
“…Besides acting directly on NKT cells and enhancing their activity against TAMs, locally produced IL-15 is expected to activate other antitumor immune effector cells, such as NK and tumor-specific CD8 + T cells (55). In contrast to IL-2, IL-15 does not fully activate Tregs (56), which are known to have an inhibitory effect on NKT cells (57) and could counteract their antitumor activity. To ensure the safety of the potential clinical use of NKT/IL-15 cells, we incorporated a suicide gene, iCasp-9, which allows the elimination of transgeneic cells upon its pharmacologic activation with a nontoxic small molecular drug, AP20187 (58)(59)(60).…”
Section: Discussionmentioning
confidence: 99%
“…Besides acting directly on NKT cells and enhancing their activity against TAMs, locally produced IL-15 is expected to activate other antitumor immune effector cells, such as NK and tumor-specific CD8 + T cells (55). In contrast to IL-2, IL-15 does not fully activate Tregs (56), which are known to have an inhibitory effect on NKT cells (57) and could counteract their antitumor activity. To ensure the safety of the potential clinical use of NKT/IL-15 cells, we incorporated a suicide gene, iCasp-9, which allows the elimination of transgeneic cells upon its pharmacologic activation with a nontoxic small molecular drug, AP20187 (58)(59)(60).…”
Section: Discussionmentioning
confidence: 99%
“…23,24 Our finding that IL-21 cannot substitute for IL-2 in supporting Treg homeostasis ( Figure 5B) is consistent with previous observations that IL-21 is unable to substitute for IL-2 in driving Treg proliferation. [31][32][33] The significance of this lack of redundancy is that cytokines that alter IL-2 availability probably have a marked impact on Treg homeostasis. In this respect, it has recently been shown that IL-27 can negatively regulate the Treg population by down-regulating Tconv IL-2 production.…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32] Longitudinal monitoring of the CD8 T cells compartment will be needed to document the differentiation from naive to TEMRA cells. Before transplantation, an increase of TEMRA CD8 T cells and a decrease of naive CD8 T cells were associated with a lower risk of acute rejection.…”
Section: Cd28mentioning
confidence: 99%